2004
DOI: 10.1038/sj.gt.3302221
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and trafficking of DNA in keratinocytes: evidence for DNA-binding proteins

Abstract: The skin is an interesting organ for human gene therapy due to accessibility, immunologic potential and synthesis capabilities. In this study, we attempted to visualize and measure the uptake of naked FITC-labeled plasmid by FACS analysis detecting up to 15% internalization in a doseand time-dependent manner. Cycloheximide treatment inhibited the uptake by 490%, suggesting a protein-mediated uptake. The inhibition of different internalization pathways demonstrated that blocking macropinocytosis (by amiloride a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 72 publications
3
45
0
2
Order By: Relevance
“…37 In human keratinocytes, two plasma membrane-actin linkers, ezrin and moesin, were identified as DNA-binding proteins. 38 Using southwestern analysis and gel shift and supershift assays, the authors found that these proteins were able to bind plasmid DNA, l-phage DNA, ODNs irrespective of their sequences and calf thymus DNA, but not RNA. On the other hand, Benimetskaya et al 39 demonstrated the ability of Mac-1 to bind ODNs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 In human keratinocytes, two plasma membrane-actin linkers, ezrin and moesin, were identified as DNA-binding proteins. 38 Using southwestern analysis and gel shift and supershift assays, the authors found that these proteins were able to bind plasmid DNA, l-phage DNA, ODNs irrespective of their sequences and calf thymus DNA, but not RNA. On the other hand, Benimetskaya et al 39 demonstrated the ability of Mac-1 to bind ODNs.…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38][39][40] It has been reported that an 80 kDa protein mediates the transport of ODNs in HL-60 cells. 36 The authors reported that ODNs binding was sequence independent and could be inhibited by 60-80% by twofold excess (25 mM) of unlabeled ODNs, as well as by desoxyribonucleotides, ribonucleotides, plasmid DNA and yeast tRNA.…”
Section: Discussionmentioning
confidence: 99%
“…FITC-and Cy5-labeled plasmid DNA was applied together with specific inhibitors of macropinocytosis (amilorid and N,N-dimethylamilorid), potocytosis (nystatin and filipin) and clathrin-coated pits (chlorpromazine). 51 These experiments suggested that macropinocytosis was the predominant mode of DNA uptake by keratinocytes.…”
Section: Skin Gene Therapy Ur Henggementioning
confidence: 97%
“…pinocytosis) seem to be involved. 51 In this study, we attempted to visualize and measure uptake of naked FITC-labeled plasmid by FACS analysis detecting up to 15% internalization in a dose-and time-dependent manner. While oligodeoxynucleotides were rapidly and almost completely taken up into the nucleus of keratinocytes, only low amounts of FITC-labeled plasmid could be detected in the cytoplasm and around the nucleus after 6 h (Figure 4).…”
Section: Skin Gene Therapy Ur Henggementioning
confidence: 99%
See 1 more Smart Citation